2015
DOI: 10.4172/2376-0419.1000143
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions towards Implementation of Dispensing Separation: Results from a Cross Sectional Analysis

Abstract: The Malaysian healthcare system has yet to introduce a legislature that implements separation of physicians and pharmacists roles. More recently, a proposal was offered to take the Malaysian populations point of view towards dispensing separation. Therefore, the current study is aimed to assess general public perceptions towards implementation of dispensing separation in the state of Penang, Malaysia. A cross-sectional study design was adopted to conduct the study. A pre-validated questionnaire was offered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…The results of this study as presented in Table indicate that most respondents were aware of pharmacists’ role in dispensing medicines, which corroborated the findings of a previous study and may be the result of efforts such as the “Know Your Pharmacist” and “Know Your Medicines” campaigns, which have focused on the role of pharmacists as medicines experts . This is also reflected in the respondents’ agreement that pharmacist checking of prescriptions was an important aspect of ensuring medication safety, that pharmacists were more knowledgeable than physicians with regard to medications and that they would prefer to receive consultations regarding medications at community pharmacies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of this study as presented in Table indicate that most respondents were aware of pharmacists’ role in dispensing medicines, which corroborated the findings of a previous study and may be the result of efforts such as the “Know Your Pharmacist” and “Know Your Medicines” campaigns, which have focused on the role of pharmacists as medicines experts . This is also reflected in the respondents’ agreement that pharmacist checking of prescriptions was an important aspect of ensuring medication safety, that pharmacists were more knowledgeable than physicians with regard to medications and that they would prefer to receive consultations regarding medications at community pharmacies.…”
Section: Discussionsupporting
confidence: 89%
“…The Malaysian Pharmaceutical Society has, in recent years, led campaigns promoting the role of pharmacists and the awareness of dispensing separation, because a lack of public knowledge is perceived as one of the main barriers to a policy shift. Several studies have attempted to explore the issue, particularly focusing on public knowledge and perceptions on the separation system itself . However, it is crucial to recognise public perception and support should be framed within the broader context of pharmacist roles, current dispensing practices, the Malaysian healthcare system and perceived readiness to implement such a policy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This puts the decision back to the consumers themselves, rather than the government taking sides . Indeed, the majority of respondents in a recent study viewed community pharmacists as being better equipped to dispense medicines compared to general practitioners, who were also perceived as having the tendency to overcharge for medicines supplied in the absence of consumer options …”
Section: Discussionmentioning
confidence: 99%
“…However, this will not be a major issue if pharmacies are co‐located within the vicinity of clinics and would be a slight inconvenience (if any) in return for patient safety. Furthermore, a recent local survey among consumers had reported that the majority of participants supported implementation of dispensing separation . Alternative models to pharmacy services in rural areas and whether incorporating a pharmacist into GP clinics in rural areas may be suitable options to consider in order to overcome issues with accessibility and convenience.…”
Section: Convenience Accessibility and Costsmentioning
confidence: 99%